Relation Between Gender and Concomitant Medications With Erythropoietin-Treatment on Wound Healing in Burn Patients. Post Hoc Subgroup-Analysis of the Randomized, Placebo-Controlled Clinical Trial “EPO in Burns” - Günter, Christina Irene; Ilg, Felicitas Paula; Hapfelmeier, Alexander; Egert-Schwender, Silvia; Jelkmann, Wolfgang; Giri, Shibashish; Bader, Augustinus; Machens, Hans-Günter; , and EPO in Burns Study Group (Frontiers in Pharmacology, 2022)
Burns are leading causes of mortality and morbidity, including prolonged hospitalization, disfigurement, and disability. Erythropoietin (EPO) is a well-known hormone causing erythropoiesis. However, EPO may play a role in healing acute and chronic wounds due to its anti-inflammatory and pro-regenerative effects. Therefore, the large, prospective, placebo-controlled, randomized, double-blind, multi-center clinical trial “EPO in Burns“ was initiated to investigate the effects of EPO versus placebo treatment in severely burned patients. The primary endpoint of „EPO in Burns“ was defined as the time elapsed until complete re-epithelialization of a defined split skin graft donor site. Additional analyses of post hoc defined subgroups were performed in view of the primary endpoint. The verum (n 45) and control (n 39) groups were compared with regard to the time it took for study wounds (a predefined split skin graft donor site) to reach the three stages of wound healing (re-epithelialization levels). In addition, the effects of gender (females n 18) and concomitant medications (insulin (n 36), non-steroidal anti-inflammatory drugs (NSAIDs) (n 41), and vasopressor agents (n 43)) were tested. Life tables were used to compare study groups (EPO vs. placebo) within subgroups. The Cox regression model was applied to evaluate interactions between the study drug (EPO) and concomitant medications for each re-epithelialization level. Using our post hoc defined subgroups, we observed a lower chance of wound healing for women compared to men (in terms of hazard ratio: hr100%: 5.984 (95%-CI: [0.805-44.490], P = 0.080)) in our study population, regardless of the study medication. In addition, results indicated an earlier onset of re-epithelialization in the first days of EPO treatment (EPO: 10% vs. Placebo: 3%). Moreover, the interpretation of the hazard ratio suggested EPO might have a positive, synergistic effect on early stages of re-epithelialization when combined with insulin (hr50%: 1.307 (P = 0.568); hr75%: 1,199 (P = 0.715)), as well as a stabilizing effect on critically ill patients (reduced need for vasopressors in the EPO group (EPO: 44% vs. Placebo 59%)). However, additional high-quality data from clinical trials designed to address these endpoints are are required to gain further insight into these effects.